Ground compaction zone of structures and structural strength of soil - Alikonis, A. (Journal of Civil Engineering and Management, 1995)
Ground compaction zone develops under action of structure foundation. Boundaries of it could be limited by a distance at which pressure from structure action is equal to structural strength of the soil. The structural strength of soil can be expressed by the parameters of shear resistance—the cohesion and the angle of the internal friction. These parameters are obtained by the experiment and corresponded to the strength at the beginning of the soil movement The ground compaction zone of structure will be at a depth, where the values of additional pressure is equal to the value of the structural strength of soil.Using the theory of soil limits the formula for the calculation of the structural strength state could be obtained:where c—soil cohesion; Φ—the angle of the internal friction. Values c and Φ are obtained experimentally. They corresponds to the strength when shear movement starts.Article in Lithuanian.Pastato pagraindo deformacijų zona ir grunto strukūrinis stipumasFirst Published Online: 26 Jul 2012